Social Conflict in the Novel Orang-Orang Proyek by Ahmad Tohari - Alamsyah; Gazali; Hasnur Ruslan; Agustan; Nirmayanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The focus of this research is to describe the social conflict in the novel "Orang-Orang Proyek" by Ahmad Tohari. This research uses a sociological perspective of literature based on the Theory of Power and Domination (Ralf Dahrendorf). Dahrendorf developed Marx's theory with a greater emphasis on authority structures within social organizations. The method used in this research is a qualitative descriptive method using textual analysis. The data source for this research is the novel "Orang-Orang Proyek" by Ahmad Tohari. The data collection technique used in this research is library research using written data sources. Three data analysis techniques are used in this study: data reduction, data presentation, and conclusion drawing. The results of this study reveal eight structural conflicts, fifteen class conflicts, and fourteen political and economic conflicts throughout the story.